2022
DOI: 10.3390/jpm12020231
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Acceptability of a Home-Based Peripheral Blood Collection Device for Viral Load Testing in the Context of Analytical Treatment Interruptions in HIV Cure Trials: Results from a Nationwide Survey in the United States

Abstract: Frequent viral load testing is necessary during analytical treatment interruptions (ATIs) in HIV cure-directed clinical trials, though such may be burdensome and inconvenient to trial participants. We implemented a national, cross-sectional survey in the United States to examine the acceptability of a novel home-based peripheral blood collection device for HIV viral load testing. Between June and August 2021, we distributed an online survey to people with HIV (PWH) and community members, biomedical HIV cure re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…It may also be possible to increase sample collection by improving local blood flow with the use of heating packs. Our finding that most participants preferred homebased sampling over coming into clinic is consistent with conclusions from three other studies, [5,7,20] but whether these reported preferences will translate to consistent use of kits for HB-PrEP is uncertain. Chasco, et al found that the majority of individuals who were offered a home monitoring option did not prefer self-collection of blood and that use of home kits was associated with Fig.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…It may also be possible to increase sample collection by improving local blood flow with the use of heating packs. Our finding that most participants preferred homebased sampling over coming into clinic is consistent with conclusions from three other studies, [5,7,20] but whether these reported preferences will translate to consistent use of kits for HB-PrEP is uncertain. Chasco, et al found that the majority of individuals who were offered a home monitoring option did not prefer self-collection of blood and that use of home kits was associated with Fig.…”
Section: Discussionsupporting
confidence: 85%
“…The pilot study was approved by the University of Washington's Human Subjects Division and institutional review board (STUDY00009004) and Public Health-Seattle & King County's Research Administrative Review Committee [20]. All participants completed written or electronic informed consent to participate in all aspects of the study.…”
Section: Abbreviationsmentioning
confidence: 99%
“… 10 Although not all PCS approaches are less painful than traditional venous blood collection, many PCS devices are less painful due to the size of the microneedles used and location of the sample collection. Surveys of patients have shown that patients prefer at‐home sampling over in‐clinic venous blood collections 3 , 11 and patients report less pain with upper arm capillary blood sampling devices compared to venous blood collection. 12 , 13 Diminished collection volumes result in significant reduction in the total amount of blood drawn per participant.…”
Section: Value Proposition Of Patient‐centric Samp...mentioning
confidence: 99%
“…This novel approach has been strongly recommended by patient advocacy groups and encouraged as well by health regulatory authorities. 1 , 2 , 3 …”
Section: Introductionmentioning
confidence: 99%
“…Already, there are at least two reported cases of sexual transmission during ATI for vaccine studies [ 39 , 40 ]. Implementation of ATI during HIV cure-related clinical trials is a necessity, yet the modalities are complex and the outcomes unpredictable [ 41 , 42 ]. There are currently no biomarkers to predict viral rebound, despite ongoing research [ 38 , 43 , 44 ]; therefore, frequent viral load measurements, often once week, must be done to inform when ART should be resumed [ 45 ].…”
Section: Acceptability Of Treatment Interruptionsmentioning
confidence: 99%